Kupffer cells ameliorate hepatic insulin resistance induced by high-fat diet rich in monounsaturated fatty acids: the evidence for the involvement of alternatively activated macrophages - Papackova, Zuzana; Palenickova, Eliska; Dankova, Helena; Zdychova, Jana; Skop, Vojtech; Kazdova, Ludmila; Cahova, Monika (Nutrition & metabolism, 2012)
BACKGROUND: Resident macrophages (Kupffer cells, KCs) in the liver can undergo both pro- or anti-inflammatory activation pathway and exert either beneficiary or detrimental effects on liver metabolism. Until now, their role in the metabolically dysfunctional state of steatosis remains enigmatic. Aim of our study was to characterize the role of KCs in relation to the onset of hepatic insulin resistance induced by a high-fat (HF) diet rich in monounsaturated fatty acids. METHODS: Male Wistar rats were fed either standard (SD) or high-fat (HF) diet for 4 weeks. Half of the animals were subjected to the acute GdCl3 treatment 24 and 72 hrs prior to the end of the experiment in order to induce the reduction of KCs population. We determined the effect of HF diet on activation status of liver macrophages and on the changes in hepatic insulin sensitivity and triacylglycerol metabolism imposed by acute KCs depletion by GdCl3. RESULTS: We found that a HF diet rich in MUFA itself triggers an alternative but not the classical activation program in KCs. In a steatotic, but not in normal liver, a reduction of the KCs population was associated with a decrease of alternative activation and with a shift towards the expression of pro-inflammatory activation markers, with the increased autophagy, elevated lysosomal lipolysis, increased formation of DAG, PKCε activation and marked exacerbation of HF diet-induced hepatic insulin resistance. CONCLUSIONS: We propose that in the presence of a high MUFA content the population of alternatively activated resident liver macrophages may mediate beneficial effects on liver insulin sensitivity and alleviate the metabolic disturbances imposed by HF diet feeding and steatosis. Our data indicate that macrophage polarization towards an alternative state might be a useful strategy for treating type 2 diabetes.